The professional culture and social technologies: theoretical and methodological analysis of their mutual connection - Kochergin, Vyacheslav Ya. (Journal of the Belarusian State University. Sociology, 2019)
The article is devoted to the study of the phenomena of the professional culture and social technologies, in their mutual relations; the article examines the ontological, typological and procedural characteristics of these phenomena. The mechanisms of their interaction are considered. Particularly at the macrolevel, this mechanism is implemented through social policy in the form of public administration. On the mesolevel it is carried out by means of technologies of formation of professional and usage of professional and corporate culture of the organizations. At the microlevel, the interaction is carried out through the «role ensemble» and the corresponding values and norms.